UPM releases exclusive Gold Bar, ‘Setem Ku Korporat’ for Golden Jubilee Celebration - Universiti Putra Malaysia, Pusat Strategi dan Perhubungan Korporat (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2021)
SERDANG - Universiti Putra Malaysia (UPM) has released an ‘Exclusive Gold Bar’ and ‘Setem Ku Korporat’ (commemorative stamps) for the first time to commemorate UPM’s Golden Jubilee Celebration in conjunction with its 50th Anniversary (1971-2021).